Health Care Providers’ Readiness to Identify and Respond to Intimate Partner Violence - Renner, Lynette M. (Journal of interpersonal violence, 2021)
Screening rates for intimate partner violence (IPV) among most health care providers are low; yet, positive interactions with providers can benefit people who experience IPV, with respect to increased safety, support, and self-efficacy. Missing is a broad assessment and comparison of knowledge, attitudes, and behavior across the range of providers who are likely to be involved in a response to IPV disclosure. The purpose of our study was to assess health care providers’ IPV preparation, knowledge, opinions, and practices and examine differences across three types of health care providers (medical providers, nursing staff, and social/behavioral health providers). We used an anonymous online survey to gather self-reported information on preparation, knowledge, opinions, and practices around IPV. A random sample of 402 providers was drawn from 13 clinics in a large multispecialty outpatient practice setting. The respondents (N = 204) consisted of medical providers (n = 70), nursing staff (n = 107), and social/behavioral health providers (n = 27). Data analyses consisted of univariate, bivariate, and multivariate analyses. Social/behavioral health providers reported more preparation, knowledge, victim understanding, and less job-related constraints, yet they reported lower screening rates than medical providers and nursing staff. Overall, no provider group seemed well-equipped to work with patients who disclose IPV. Our findings identify unmet needs within our health system to better train health care providers and restructure care models to support IPV identification and response. A focus on interprofessional training and care collaboration would bolster competency and reduce constraints felt by the health care workforce.